Implementation of Lesson Study Based Collaborative Learning: Analysis of Improving Science Learning Achievement of Elementary School Students during Pandemic Covid-19 - Hamna Hamna; Muh. Khaerul Ummah BK (Universitas Muhammadiyah Mataram, 2021)
The purpose of this study was to analyze data related to the application of collaborative learning based on lesson study on science learning achievement of elementary school students during the implementation of PPKM Level 3 in the Pandemic Covid-19 situation. The research method used was True Experiment Design which was analyzed with a quantitative approach. Based on the sampling technique used, namely simple random sampling, 30 students were assigned as research samples which were then divided into two small classes, namely class A (experimental class) and class B (control class). To assist the smooth running of the research, an observation sheet instrument was used (Plan, Do, and See). The results showed that the implementation of lesson study based learning was carried out with a very good assessment. As presented in the Plan Phase, Do Phase and See Phase, respectively from Meeting I (73.48%), Meeting II (75.83%), Meeting III (85.42%), and Meeting IV (92.55 %). From these findings, it also affects the increase in science learning achievement with a significant level of influence, namely 94%.